PENGARUH EMPOWERMENT LEADERSHIP DAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD NEGERI WILAYAH ILIR TIMUR - Weni Agustina; Dessy Wardiah; Andi Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine and analyze (1) the influence of Empowerment Leadership on Teacher Performance in Elementary Schools in the East Ilir Region (2) the influence of managerial ability on Teacher Performance in Elementary Schools in the East Ilir Region. (3). the influence of Empowerment Leadership and managerial ability together on Teacher Performance in Elementary Schools in the East Ilir Region. This study is a descriptive method study with a quantitative approach. This study was conducted in Elementary Schools in the East Ilir Region, with a sample of 101 Elementary School teachers in the East Ilir Region. Data collection techniques used questionnaires and documentation. The validity test used construct validity, while the reliability test used Cronbach's Alpha. The prerequisite analysis test used the normality test, Heteroscedasticity Test, and Multicollinearity Test, and the data was analyzed using multiple linear regression techniques, correlation, t-test and F-test. The results of the study showed that: 1) Empowerment Leadership had a significant effect on Teacher Performance in Elementary Schools in the East Ilir Region (2) Managerial ability had a significant effect on Teacher Performance in Elementary Schools in the East Ilir Region. (3). Empowerment Leadership and managerial skills have a significant influence together on Teacher Performance at Public Elementary Schools in the East Ilir Region. Keywords: Empowerment Leadership, Principal Managerial Ability, Teacher Performance